Pengaruh Inovasi Produk, Persepsi Harga, dan Media Sosial terhadap Keputusan Pembelian pada Restoran Samchick Sambi - Elfa Yunita; Muhammad Alhada Fuadilah Habib (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Samchick Sambi is a business in the food and beverage sector that was founded in 2018. Even though this business is still new and amidst a lot of competition with similar products, the Samchick Sambi restaurant has succeeded in achieving high and relatively stable sales. Samchick Sambi always provides innovative products at affordable prices, providing good price perception, and creative marketing through social media platforms. This research aims to determine the influence of product innovation, price perceptions, and social media on consumer purchasing decisions for the Samchick Sambi restaurant. This research uses a quantitative approach with the type of research used, namely associative. The population is consumers who have made purchases at Samchick Sambi. Data analysis used multiple regression with the help of IBM SPSS 25. The research results showed that: (1) product innovation, price perception, and social media had a significant influence on consumer purchasing decisions at Samchick Sambi Restaurant. (2) product innovation has a positive and significant effect on consumer purchasing decisions at the Samchick Sambi Restaurant. (3) price perception has a positive and significant effect on consumer purchasing decisions at Samchik Sambi Restaurant. (4) social media has a positive and significant influence on consumer purchasing decisions at Samchik Sambi Restaurant.